2019
DOI: 10.1097/sla.0000000000003268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microvascular Invasion Risk on Early Recurrence of Hepatocellular Carcinoma After Surgery and Radiofrequency Ablation

Abstract: Objective: We compared surgical resection (SR) and radiofrequency ablation (RFA) as first-line treatment in patients with hepatocellular carcinoma (HCC) based on the risk of microvascular invasion (MVI). Background: The best curative treatment modality between SR and RFA in patients with HCC with MVI remains unclear. Methods: Data from 2 academic cancer center-based cohorts of patients with a single, small (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
197
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(215 citation statements)
references
References 37 publications
14
197
3
1
Order By: Relevance
“…As expected, the overall recurrence rate of lesions with HBP findings (73.7%) was much higher than those without (42.9%), confirming the reported view that the presence of HBP findings is harmful to the prognosis of HCC [12,14]. Specifically, in our study, both LTP and IDR were higher in lesions with HBP findings (LTP: 23.6%, IDR: 50.0%) than those without (LTP: 10.4%, IDR: 32.5%).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As expected, the overall recurrence rate of lesions with HBP findings (73.7%) was much higher than those without (42.9%), confirming the reported view that the presence of HBP findings is harmful to the prognosis of HCC [12,14]. Specifically, in our study, both LTP and IDR were higher in lesions with HBP findings (LTP: 23.6%, IDR: 50.0%) than those without (LTP: 10.4%, IDR: 32.5%).…”
Section: Discussionsupporting
confidence: 87%
“…They are distributed around the larger primary tumors and have the same tumor clonality as the primary lesions [33]. Obviously, the results of LTP and IDR shown in this study have further confirmed the relationship between HBP findings and MVI, as the previous literature described [12,14]. More importantly, due to the mechanism of LTP occurrence and our findings, we put forward a new hypothesis of the potential relationship between HBP findings and microsatellite foci.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study also showed that irregular arterial phase peritumoral enhancement was a significant MRI finding predicting the MVI of cHCC-CCA. Many reports [18,20,39] have shown that arterial peritumoral enhancement is an independent predictive factor of MVI in HCC. To date, few studies have described the relationship between peritumoral enhancement of cHCC-CCA and MVI.…”
Section: Discussionmentioning
confidence: 99%
“…markers such as NLR, PLR, and prognostic nutritional index; and 20,21 (5) pathological markers such as microvascular invasion and lowly-differentiated neoplasm. 22,23 But little attention has been paid to the relationship between these indicators or combined markers and prognosis of patients with HCC treated with TACE plus percutaneous ablation. However, the present study illustrated the development of a novel scoring system based on gender, tumor number, AFP, Fib, and APR selected by univariate and multivariate analysis, which might evaluate the recurrence risk of patients with HCC after undergoing combined therapies.…”
Section: Discussionmentioning
confidence: 99%